Non-Pecuniary Remedies Revisited: Expanding Influence of the ILC Articles? - Bradfield, Michelle; Attanasio, David (ICSID review, 2022)
Abstract Although non-monetary remedies for international law violations are a fixture of the International Law Commission’s Draft Articles on Responsibility of States for Internationally Wrongful Acts (ILC Articles), investor-State arbitral tribunals have considered or ordered such remedies only rarely. This article surveys the role that the ILC Articles on non-monetary remedies have, and could have, in investor-State arbitration. It first reviews how tribunals have referenced and applied the ILC Articles, or the legal principles it codifies, when grappling with their power to award non-monetary remedies, the specific content of such non-monetary remedies, and the reasons not to award such remedies. It concludes that, while the ILC Articles have increasing significance, tribunals remain hesitant to award the full range of remedies provided for in the ILC Articles. The article then addresses considerations beyond the ILC Articles that tribunals have referenced in decisions on non-monetary remedies—usually as grounds to reject non-monetary remedies. The most common is concern for the effects of such remedies on State sovereignty, but considerations less frequently raised include questions about enforceability and the need for party consent. These features indicate that some tribunals remain willing to go beyond the ILC Articles in reaching decisions on non-monetary remedies. The article finally considers what lessons may be gleaned from human rights practice on non-monetary remedies. By contrast with investor-State tribunals, human rights adjudicators have enthusiastically embraced non-monetary remedies and their practice provides insights for how such remedies may be employed in disputes between private individuals and sovereign States.